Modulation Effects of Curcumin on Erythrocyte Ion-Transporter Activity - Prabhakar Singh; Syed Ibrahim Rizvi (International Journal of Cell Biology)
Curcumin ((1E,6E)-1,7-Bis(4-hydroxy-3-methoxyphenyl)-1,6-heptadiene-3,5-dione), the yellow biphenolic pigment isolated from turmeric (Curcuma longa), has various medicinal benefits through antioxidation, anti-inflammation, cardiovascular protection, immunomodulation, enhancing of the apoptotic process, and antiangiogenic property. We explored the effects of curcumin in vitro (10−5 M to 10−8 M) and in vivo (340 and 170 mg/kg b.w., oral) on Na+/K+ ATPase (NKA), Na+/H+ exchanger (NHE) activity, and membrane lipid hydroperoxides (ROOH) in control and experimental oxidative stress erythrocytes of Wistar rats. As a result, we found that curcumin potently modulated the membrane transporters activity with protecting membrane lipids against hydro-peroxidation in control as well as oxidatively challenged erythrocytes evidenced by stimulation of NKA, downregulation of NHE, and reduction of ROOH in the membrane. The observed results corroborate membrane transporters activity with susceptibility of erythrocyte membrane towards oxidative damage. Results explain the protective mechanism of curcumin against oxidative stress mediated impairment in ions-transporters activity and health beneficial effects.